2012
DOI: 10.1097/mph.0b013e3182465b58
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anaplastic Wilms Tumor and Subsequent Relapse in a Child With Diaphanospondylodysostosis

Abstract: Diaphanospondylodysostosis (DSD) is a rare skeletal dysplasia syndrome resulting from disordered mesenchymal differentiation. Children with DSD generally die in utero or during the first month of life from severe thoracic insufficiency syndrome. An association of DSD with nephroblastomatosis has been observed, but the natural history of such nephroblastomatosis remains poorly characterized due to the rarity of the underlying condition. We describe a patient with DSD who developed bilateral hyperplastic nephrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The knockout mouse phenotype is recapitulated by the manifestations in patients with BMPER mutations. The most prominent features are vertebral segmentation anomalies and kidney abnormalities [ 2 4 , 7 9 , 11 ]. Kidney abnormalities (cysts and nephroblastomatosis) have been reported in most patients with DSD [ 7 11 ], but only in some patients with ISD [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knockout mouse phenotype is recapitulated by the manifestations in patients with BMPER mutations. The most prominent features are vertebral segmentation anomalies and kidney abnormalities [ 2 4 , 7 9 , 11 ]. Kidney abnormalities (cysts and nephroblastomatosis) have been reported in most patients with DSD [ 7 11 ], but only in some patients with ISD [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two other patients diagnosed with DSD survived past the neonatal period. One died of nephroblastoma shortly before turning 5 years of age (Scottoline et al, 2012;Tasian, Kim, Miniati, & DuBois, 2012;Vatanavicharn et al, 2007). The forementioned patient was discussed in three separate articles.…”
Section: Discussionmentioning
confidence: 99%
“… in 2011. Two papers from 2012 report of two infants with DSD, who survived longer and developed anaplastic Wilms tumor of both kidneys at the age of 18 and 20 months and died at the age 4 and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in 2010, Funari et al [4] identified mutation in the BMPER gene as underlying cause of DSD, which was confirmed by Ben-Neriah et al [5] in 2011. Two papers from 2012 [6,7] report of two infants with DSD, who survived longer and developed anaplastic Wilms tumor of both kidneys at the age of 18 and 20 months and died at the age 4 and 5 years, respectively. Increased nuchal translucency is a leading ultrasonographic sign of chromosomal disorder but is also observed in skeletal dysplasias such as osteogenesis imperfecta, achondrogenesis, thanatophoric dwarfism, and asphyxiating thoracic dystrophy.…”
Section: Discussionmentioning
confidence: 99%